-1=x is the answer I’m pretty sure
Answer:
5 and 6
Step-by-step explanation:
5 and 6
Answer:
y = -2/3 + 18
Step-by-step explanation:
2x + 3y = 18 ----- here is the equation...
-2x - 2x ----- bring the 2x to the other side
3y = -2x + 18 ----- now you have to divide everything by 3 to get y by itself
y = -2/3 + 18 ----- Done!
One solution was found : t ≤ -13 (number 4)
Pull out like factors :
-3t - 39 = -3 • (t + 13)
Divide both sides by -3
Remember to flip the inequality sign:
Solve Basic Inequality :
Subtract 13 from both sides to get t≤−13